Factor Validation of a Fidelity of Implementation Measure for Social Behavior Systems. (February 2019) - Massar, Michelle M.; McIntosh, Kent; Mercer, Sterett H.
Assessing fidelity of implementation of school-based interventions is a critical factor in successful implementation and sustainability. The Tiered Fidelity Inventory (TFI) was developed as a comprehensive measure of all three tiers of School-Wide Positive Behavioral Interventions and Supports (SWPBIS) and is intended to measure the extent to which the core features of SWPBIS are implemented with fidelity. The purpose of this study was to assess the extent to which the TFI can be used as one measure of all three tiers, three separate measures of individual tiers, or as a more granular level of fidelity that measures implementation on 10 subscales across the tiers. A confirmatory factor analysis was conducted to validate the factor structure of the TFI. Results indicate that the TFI is a valid measure of fidelity of implementation of SWPBIS and can be used to measure implementation by subscales, tiers, and as a comprehensive assessment of all three tiers.